True Highland spirit - Forester, Amanda (Sourcebooks Casablanca, 2012)
in 1355, Morrigan McNab is a Highland lady, robbed of her birthright and with no choice but to fight alongside her brothers to protect their impoverished clan. When she encounters Sir Jacques Dragonet, she discovers her fiercest opponent. He will give his life to defend Scotland from the English. But he can't stop himself from admiring the beautiful Highland lass who wields her weapons as skillfully as he does, and endangers his heart even more than his life.